Polar vortices on Earth and Mars: A comparative study of the climatology and variability from reanalyses. (12th June 2014) - Mitchell, D. M.; Montabone, L.; Thomson, S.; Read, P. L.
Abstract Polar vortices on Mars provide case‐studies to aid understanding of geophysical vortex dynamics and may help to resolve long‐standing issues regarding polar vortices on Earth. Due to the recent development of the first publicly available Martian reanalysis dataset (MACDA), for the first time we are able to characterise thoroughly the structure and evolution of the Martian polar vortices, and hence perform a systematic comparison with the polar vortices on Earth. The winter atmospheric circulations of the two planets are compared, with a specific focus on the structure and evolution of the polar vortices. The Martian residual meridional overturning circulation is found to be very similar to the stratospheric residual circulation on Earth during winter. While on Earth this residual circulation is very different from the Eulerian circulation, on Mars it is found to be very similar. Unlike on Earth, it is found that the Martian polar vortices are annular, and that the Northern Hemisphere vortex is far stronger than its southern counterpart. While winter hemisphere differences in vortex strength are also reported on Earth, the contrast is not as large. Distinctions between the two planets are also apparent in terms of the climatological vertical structure of the vortices, in that the Martian polar vortices are observed to decrease in size at higher altitudes, whereas on Earth the opposite is observed. Finally, it is found that the Martian vortices are less variable through the winter than on Earth, especially in terms of the vortex geometry. During one particular major regional dust storm on Mars (Martian year 26), an equatorward displacement of the vortex is observed, sharing some qualitative characteristics of sudden stratospheric warmings on Earth.